Factors Affecting Factor XIII Assay by Dansyl Cadaverine Incorporation - Sheltawy, Marion J.; Miloszewski, Krzysztof; Losowsky, Monty S. (Thrombosis and Haemostasis, 1972)
Factors affecting the activation of factor XIII and its subsequent action in incorporating the fluorescent amine, dansyl cadaverine, into casein have been investigated.A comparison of the activation of factor XIII at 30° C and 37° C using 5 NIH units Maws bovine thrombin showed that increasing the temperature shortened the time required for maximal activity from 4-10 minutes to 4 minutes. A sharper peak of activity was observed at the higher temperature and a more rapid fall with increasing activation time. At 30° C, 25 units Parke Davis thrombin topical gave similar results to 5 units Maws thrombin topical.When an activation period of 10 minutes was selected, 5 units of thrombin gave the highest values of factor XIII activity.The optimal level of calcium in the incubation medium was found to be 12 mM.